Diastereoselective Synthesis of a Highly Substituted cis-Decahydroquinoline via a Knoevenagel Condensation - Huang, Junfeng (2008)
A diastereoselective approach to 3,7,8-trisubstituted cis-decahydroquinolines is described. This ring system forms the core of rings B and E of the norditerpenoid alkaloid methyllycaconitine. This approach starts with a known disubsituted cyclohexene. The remaining carbons are attached via a Knoevenagel condensation followed by an intramolecular lactam formation. The stereochemistry of the substituents is controlled by the cis-substitution of the starting cyclohexene ring.